Inosine 5′-Monophosphate Dehydrogenase Activity for the Longitudinal Monitoring of Mycophenolic Acid Treatment in Kidney Allograft Recipients. Issue 4 (1st June 2020) - Glander, Petra; Waiser, Johannes; Hambach, Pia; Bachmann, Friederike; Budde, Klemens; Eckardt, Kai-Uwe; Friedersdorff, Frank; Gaedeke, Jens; Kron, Susanne; Lorkowski, Christine; Mai, Marco; Neumayer, Hans-H.; et al.
Abstract : Background: Mycophenolic acid (MPA) is a standard immunosuppressant in organ transplantation. A simple monitoring biomarker for MPA treatment has not been established so far. Here, we describe inosine 5′-monophosphate dehydrogenase (IMPDH) monitoring in erythrocytes and its application to kidney allograft recipients. Methods: IMPDH activity measurements were performed using a high-performance liquid chromatography assay. Based on 4203 IMPDH measurements from 1021 patients, we retrospectively explored the dynamics early after treatment start. In addition, we analyzed the influence of clinically relevant variables on IMPDH activity in a multivariate model using data from 711 stable patients. Associations between IMPDH activity and clinical events were evaluated in hospitalized patients. Results: We found that IMPDH activity reflects MPA exposure after 8 weeks of constant dosing. In addition to dosage, body mass index, renal function, and coimmunosuppression affected IMPDH activity. Significantly lower IMPDH activities were found in patients with biopsy-proven acute rejection as compared to patients without rejection (median [interquartile range]: 696 [358–1484] versus 1265 [867–1618] pmol xanthosine-5′-monophosphate/h/mg hemoglobin, P < 0.001). The highest IMPDH activities were observed in hospitalized patients with clinically evident MPA toxicity as compared to patients with hospitalization not related to MPA treatment (1548 [1021–2270] versus 1072 [707–1439] pmol xanthosine-5′-monophosphate/h/mg hemoglobin; P < 0.001). Receiver operating characteristic curve analyses underlined the usefulness of IMPDH to predict rejection episodes (area, 0.662; confidence interval, 0.584-0.740; P < 0.001) and MPA-associated adverse events (area, 0.632; confidence interval, 0.581-0.683; P < 0.001), respectively. Conclusions: IMPDH measurement in erythrocytes is a novel and useful strategy for the longitudinal monitoring of MPA treatment. Abstract :